2015
DOI: 10.1007/s10055-015-0276-2
|View full text |Cite
|
Sign up to set email alerts
|

Activities of daily living assessment in spinal cord injury using the virtual reality system Toyra®: functional and kinematic correlations

Abstract: The main objective of this study was to analyze the correlations between functional scales and kinematic data collected during the execution of upper limb (UL) basic activities of daily living in an immersive virtual reality (VR) environment. Fifteen people with tetraplegia participated in the study. Moreover, we also want to confirm if changes in UL functional performance detected by functional scales are also detected by the VR system Toyra Ò . Patients were assessed before and after 4 weeks of daily convent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In the past decade, we have seen significant scientific breakthrough in the arena of assistive technology and robotics in rehabilitation ( 26 28 ). Literature on innovative rehabilitation technology such as virtual reality has shown that it was useful in reducing neuropathic pain ( 29 ), enhancing rehabilitation of upper limb function ( 30 ), balance, motor recovery, as well as helping to improve user morale and participation among individuals with SCI ( 31 ). In a recent systematic review, most rehabilitation service users and caregivers found that the use of robotics in motor rehabilitation were beneficial to the physical, psychological and social well-beings, and it was well-accepted ( 32 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, we have seen significant scientific breakthrough in the arena of assistive technology and robotics in rehabilitation ( 26 28 ). Literature on innovative rehabilitation technology such as virtual reality has shown that it was useful in reducing neuropathic pain ( 29 ), enhancing rehabilitation of upper limb function ( 30 ), balance, motor recovery, as well as helping to improve user morale and participation among individuals with SCI ( 31 ). In a recent systematic review, most rehabilitation service users and caregivers found that the use of robotics in motor rehabilitation were beneficial to the physical, psychological and social well-beings, and it was well-accepted ( 32 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the use of technology in rehabilitation in combination with virtual reality (VR) environments has increased in the last years [34][35][36][37], mainly because the quantity of therapy that patients receive increases. VR has many advantages for intervention, such as enabling the grading of activities, obtaining precise performance measures, providing a safe and ecologically valid environment, and being enjoyable and motivating [24,38].…”
Section: Introductionmentioning
confidence: 99%
“…For example, White et al 10 developed a virtual kitchen that captures the participant's joint angle data during daily living tasks and used captured data to quantitatively assess the effectiveness of physical therapy. Dimbwadyo-Terrer et al 11 developed an immersive VR environment to assess upper limb performance when conducting basic daily living tasks and showed that kinematic data recorded in a VR environment highly correlated with functional scales of the upper limb. These kinematic analyses with motion capture systems could provide further opportunity to quickly assess a patient's cognitive impairment…”
Section: Introductionmentioning
confidence: 99%